Development of a microbial time-temperature integrator system using lactic acid bacteria - Lim, Seong Hwan; Choe, Woo Yeong; Son, Byung Hyun; Hong, KwangWon (Food science and biotechnology, 2014)
A microbial time-temperature integrator (TTI) system was developed using lactic acid bacteria ( Weissella koreensis ) obtained from baechukimchi . Activation energy ( Ea ), which represents the temperature dependence of the TTI response, was calculated using the Arrhenius equation. Ea values for the color change (Δ E value), maximum specific growth rate (μ max ), and pH change of the TTI measured under different isothermal conditions (5, 10, 15 and 20°C) were 99.88, 95.91, and 93.38 kJ/mol, respectively. According to the time taken to reach the TTI endpoint by the initial inoculum level of W. koreensis (6.2, 5.5, 4.5, and 3.4 log CFU/mL), a negative correlation was observed in 63.5, 101.8, 115.1 and 166.6 h. In addition, initial bacterial counts decreased significantly up to almost 4% at 20°C in 3 months when W. koreensis viability was measured at the freezing point of the microbial TTI system (20 and −80°C) for 1 week, 1 month, 2 months, and 3 months. However, viability was about 95% at 80°C. This microbial TTI system would be useful to monitor the quality of food with similar Ea values during storage or distribution.